2012
DOI: 10.1063/1.4764020
|View full text |Cite
|
Sign up to set email alerts
|

Reconfigurable liquid metal circuits by Laplace pressure shaping

Abstract: We report reconfigurable circuits formed by liquid metal shaping with <10 pounds per square inch (psi) Laplace and vacuum pressures. Laplace pressure drives liquid metals into microreplicated trenches, and upon release of vacuum, the liquid metal dewets into droplets that are compacted to 10-100Â less area than when in the channel. Experimental validation includes measurements of actuation speeds exceeding 30 cm/s, simple erasable resistive networks, and switchable 4.5 GHz antennas. Such capability may be of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
76
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 96 publications
(77 citation statements)
references
References 22 publications
1
76
0
Order By: Relevance
“…This capability enables previously unidentified types of electrohydrodynamic phenomena to manipulate the shape of metal, which is attractive for a wide range of applications including microelectromechanical systems (MEMS) switches and conductive microcomponents (35), microactuators and pumps (36), adaptive electronic skins (37), tunable antennas and apertures (38,39), fluidic optical components and displays (40,41), field-programmable circuits (42), and metamaterials with reversible cloaking. The necessity of electrolyte and the reliance on electrochemical reactions may present some practical limitations for long-term switchability, although batteries operate with similar restrictions.…”
mentioning
confidence: 99%
“…This capability enables previously unidentified types of electrohydrodynamic phenomena to manipulate the shape of metal, which is attractive for a wide range of applications including microelectromechanical systems (MEMS) switches and conductive microcomponents (35), microactuators and pumps (36), adaptive electronic skins (37), tunable antennas and apertures (38,39), fluidic optical components and displays (40,41), field-programmable circuits (42), and metamaterials with reversible cloaking. The necessity of electrolyte and the reliance on electrochemical reactions may present some practical limitations for long-term switchability, although batteries operate with similar restrictions.…”
mentioning
confidence: 99%
“…By leveraging these unique characteristics, researchers have recently demonstrated advances in reconfigurable, responsive, and stretchable electronic devices. [5][6][7][8] Select applications of liquid metals include soft electronic skins, [9,10] dynamic and flexible antennas, [11][12][13][14] and self-healing and elastic electronics. [15,16] Moreover, the fluid nature of GaLMAs such as eutectic gallium-indium (eGaIn) enables broad process compatibility with additive printing methods such as direct write, inkjet, transfer, and 3D printing.…”
mentioning
confidence: 99%
“…In Cumby, et al, 46 reconfigurable circuits were demonstrated using mercury. However, transferability of these results to non-toxic gallium-alloys is challenging due to the adhesive nature of gallium-oxide.…”
Section: Controlled Wettingmentioning
confidence: 98%